Efect of draft an Meloidogyne exigua (Nemata) infestation on coffee’s root growth an yield - Barbosa, Dimmy Herllen Silveira Gomes; Vieira, Henrique Duarte; Rodrigues, Weverton Pereira; Filho, Júlio Cézar Rodrigues; Barroso, Deborah Guerra; Silva, Thiago Rodrigues da Conceição (Coffee Science - ISSN 1984-3909, 2014)
The State of Rio de Janeiro was once the main coffee producer in Brazil, but the infestation of nematodes (Meloidogyne exigua) has caused the production decline since the nineteenth century. The use of resistant cultivars is the main measure nematode control, and the resistant genotypes can be used both grafted or not. Coffea canephora is nematode resistant and it has a more developed root system compared to C. arabica. In this study, we evaluated the root development and yield of different cultivars of C. arabica grafted (on Apoatã IAC 2258) or not, established in areas infested (CN) by, or free (SN) of M. exigua. The genotypes in the CN area had shorter roots than those in the SN area. The not-grafted Tupi and Catuai red 144 showed thicker roots in the CN area, but they were the thinner when grafted. In the CN area the average yield of six seasons for not-grafted susceptible genotypes was up to 55% less than of those genotypes grafted on IAC Apoatã 2258. In the SN area the grafted genotypes produced 41.2% less than the not-grafted ones.